Different patterns of gene silencing in position-effect variegation. - Lloyd, V.K.; Dyment, D.; Sinclair, D.A.R.; Grigliatti, T.A. (Genome, 2003)
Position-effect variegation (PEV) results when a fully functional gene is moved from its normal position to a position near to a broken heterochromatic-euchromatic boundary. In this new position, the gene, while remaining unaltered at the DNA level, is transcriptionally silenced in some cells but active in others, producing a diagnostic mosaic phenotype. Many variegating stocks show phenotypic instability, in that the level of variegation is dramatically different in different isolates or when out crossed. To test if this phenotypic instability was due to segregation of spontaneously accumulated mutations that suppress variegation, four different and well-characterized strains showing PEV for the white+ gene (wm4, wmMc, wm51b, and wmJ) and representing both large and small spot variegators were repeatedly out crossed to a strain free of modifiers, and the phenotypes of these variegators were monitored for 30 generations. Once free of modifiers, these variegating strains were then allowed to reaccumulate modifiers. The spontaneous suppressors of variegation were found to include both dominant and recessive, autosomal and X-linked alleles selected to reduce the detrimental effects of silencing white+ and adjacent genes. The time of peak sensitivity to temperature during development was also determined for these four variegators. Although large and small spot variegators have previously been attributed to early and late silencing events, respectively, the variegators we examined all shared a common early period of peak sensitivity to temperature. Once free of their variegation suppressors, the different variegating strains showed considerable differences in the frequency of inactivation at a cellular level (the number of cells showing silencing of a given gene) and the extent of variegation within the cell (the number of silenced genes). These results suggest that large and small spot variegation may be a superficial consequence of spontaneous variegation suppressors. The nature and number of these spontaneous variegation suppressors depends on the number of genes silenced in a given variegating rearrangement. These results are interpreted in the context of a model that proposes that the different underlying patterns of gene silencing seen in PEV can be attributed directly to the formation of heterochromatin domains possessing different properties of propagation during cell division.